TINJAUAN HUKUM ISLAM TENTANG TRANSAKSI E-COMMERCE APLIKASI SHOPEE DENGAN METODE PAYLATER - Nadiyah Mawaddaha; Rezkia Zahara Lubis (Sharia Law and Justice Journal, 2025)
Shopee is an application that is engaged in buying and selling online and can be accessed easily by using a smartphone. This application provides various types of payments, one of which is shopee paylater / pay later. Pay Later is a payment method that supports consumers to “buy now, pay later”. With this payment method, consumers are given the opportunity to buy something without having to pay for a certain period of time. In the Islamic view, this paylater transaction is usury.